Noninvasive Positive-Pressure Ventilation in Acute Respiratory Distress Syndrome in Patients With Acute Pancreatitis: A Retrospective Cohort Study. Issue 1 (January 2016) - Zhao, Xianlin; Huang, Wei; Li, Juan; Liu, Yiling; Wan, Meihua; Xue, Guijun; Zhu, Shifeng; Guo, Hui; Xia, Qing; Tang, Wenfu
Abstract : Objectives: Noninvasive positive-pressure ventilation (NPPV) in acute respiratory distress syndrome (ARDS) is controversial. We aimed to assess the efficacy of NPPV on ARDS in acute pancreatitis (AP). Methods: In this retrospective, single-center cohort study, demographic data, clinical and biochemical parameters of AP and developed ARDS on admission as well as before and after use of NPPV, and clinical outcomes were retrieved from the medical record database. Degrees of ARDS at presentation were retrospectively classified using the Berlin Definition. Results: Of 379 patients identified, 127 were eligible for inclusion and had NPPV for more than 24 hours. There were 44 mild, 64 moderate, and 19 severe patients with ARDS at presentation; endotracheal intubation rates were 0% (0/44), 23.4% (15/64), and 47.4% (9/19); and the mortality rates were 0% (0/44), 9.4% (6/64), and 15.8% (3/19), respectively. After NPPV treatment, systolic pressure, heart rate, respiratory rate, and fraction of inspired oxygen decreased, whereas oxygen saturation increased significantly in the NPPV success group compared with the failed group. Similar findings were also observed between survivors and nonsurvivors. Conclusions: Noninvasive positive-pressure ventilation may be an effective option for the initial treatment of ARDS patients in AP, but the use of NPPV should be applied prudently in the most severe cases.